ANALISIS DAN MITIGASI RISIKO RANTAI PASOK MINYAK PALA KABUPATEN ACEH SELATAN MENGGUNAKAN FMECA - Rachman Jaya, M. Ismail, Yusriana, Iskandar Mirza, Mehran, Asis, Basri A. Bakar (Jurnal Teknologi Industri Pertanian, 2019)
Nutmeg oil from South Aceh is one of the main commodities in Indonesian essential oils trading. Specially, 70-80% Indonesian nutmeg oil trading origin is from South Aceh. On the other hand, a business risk of nutmeg oil is on collectors district, so these actors to be critical point in nutmeg oil production. The objectives of this research were to determine risk factors and to design risk mitigation in nutmeg oils supply chain on South Aceh. The technique used was Failure Mode and Effective Critically Analysis (FMECA). Data collecting according to expert’s survey and background and qualification of experts were academicians, researcher, and practitioners. Academicians and researchers were PhD holders with 10 years experience in agriculture development, practitioners graduate minimally, practitioners were bachelor degree holders with 15 years experience. The result of the study showed that on farmers, the highest risks were on pest and disease attack and price fluctuation, meanwhile on agro-industry actors, the highest risks were on quality product fulfillment and price fluctuation. To arrange over supply, policy analysis was needed for the establishment of business units initiated by local governments.Keywords: nutmeg oils, South Aceh, FMECA